Small to Large Polaron Behavior Induced by Controlled Interactions in Perovskite Quantum Dot Solids - Kim, Juno; Xu, Yuanze; Bain, David; Li, Mingxing; Cotlet, Mircea; Yu, Qiuming; Musser, Andrew J. (ACS nano, 2023)
The polaron is an essential photoexcitation that governs the unique optoelectronic properties of organic-inorganic hybrid halide perovskites, and it has been subject to extensive spectroscopic and theoretical investigation over the past decade. A crucial but underexplored question is how the nature of the photogenerated polarons is impacted by the microscopic perovskite structure and what functional properties this affects. To tackle this question, we chemically tuned the interactions between perovskite quantum dots (QDs) to rationally manipulate the polaron properties. Through a suite of time-resolved spectroscopies, we find that inter-QD interactions open an excited-state channel to form large polaron species, which exhibit enhanced spatial diffusion, slower hot polaron cooling, and a longer intrinsic lifetime. At the same time, polaronic excitons are formed in competition via localized band-edge states, exhibiting strong photoluminescence but are limited by shorter intrinsic lifetimes. This control of polaron type and function through tunable inter-QD interactions not only provides design principles for QD-based materials but also experimentally disentangles polaronic species in hybrid perovskite materials.The polaron is an essential photoexcitation that governs the unique optoelectronic properties of organic-inorganic hybrid halide perovskites, and it has been subject to extensive spectroscopic and theoretical investigation over the past decade. A crucial but underexplored question is how the nature of the photogenerated polarons is impacted by the microscopic perovskite structure and what functional properties this affects. To tackle this question, we chemically tuned the interactions between perovskite quantum dots (QDs) to rationally manipulate the polaron properties. Through a suite of time-resolved spectroscopies, we find that inter-QD interactions open an excited-state channel to form large polaron species, which exhibit enhanced spatial diffusion, slower hot polaron cooling, and a longer intrinsic lifetime. At the same time, polaronic excitons are formed in competition via localized band-edge states, exhibiting strong photoluminescence but are limited by shorter intrinsic lifetimes. This control of polaron type and function through tunable inter-QD interactions not only provides design principles for QD-based materials but also experimentally disentangles polaronic species in hybrid perovskite materials.